Skotomorphogenesis exploits threonine to promote hypocotyl elongation. (22nd November 2022) - Tabeta, Hiromitsu; Higashi, Yasuhiro; Okazaki, Yozo; Toyooka, Kiminori; Wakazaki, Mayumi; Sato, Mayuko; Saito, Kazuki; Hirai, Masami Y; Ferjani, Ali
Abstract: Abstract: Mobilisation of seed storage reserves is important for seedling establishment in Arabidopsis . In this process, sucrose is synthesised from triacylglycerol via core metabolic processes. Mutants with defects in triacylglycerol-to-sucrose conversion display short etiolated seedlings. We found that whereas sucrose content in the indole-3-butyric acid response 10 ( ibr10 ) mutant was significantly reduced, hypocotyl elongation in the dark was unaffected, questioning the role of IBR10 in this process. To dissect the metabolic complexity behind cell elongation, a quantitative-based phenotypic analysis combined with a multi-platform metabolomics approach was applied. We revealed that triacylglycerol and diacylglycerol breakdown were disrupted in ibr10, resulting in low sugar content and poor photosynthetic ability. Importantly, batch-learning self-organised map clustering revealed that threonine level was correlated with hypocotyl length. Consistently, exogenous threonine supply stimulated hypocotyl elongation, indicating that sucrose levels are not always correlated with etiolated seedling length, suggesting the contribution of amino acids in this process.